URDU-A COMPARATIVE ANALYSIS OF THE JOINT AND SEPARATE FAMILY SYSTEMS IN THE LIGHT OF ISLAMIC TEACHINGS - Shabana Rafiq; Zia ur Rehman (دی اسکالر)
Islam is a complete code of life that provides guidance to its followers in all Fields of life. Islam emphasizes the development of an ideal society. The family system is the fundamental unit of any society. if excellent and healthy principles are instilled in the family structure, the resulting society will undoubtedly shine with the brilliance of righteous ideals. The holy Qur'an also emphasises the importance of family relationships and relations with relatives. Basically a family consists of men, women and their children. In any society this relationship as much as will be stronger and more stable then there will be the most peace and prosperity in the society. In Islam there are two types of family systems Joint and separate family systems. Islam has emphasized family stability, but in our society, most of the joint family system is prevalent. In this system, husband and wife, father-in-law, sister-in-law and brother-in-law etc. live in the same house. Everyone has a common food and living arrangement, which creates a lot of problems and confusions. the present article will focus on “what is the basic concept of joint and separate family systems and its solution in Islam. And what are the problems that arise in the joint family system and how can it be solved in the light of  the teaching of Islam and from the way of Islam it will be tried to see which of the joint  and separate family systems is better. However, the advantages and disadvantages will be evaluated.